A Multi-Faceted Approach to Successful Transition for Students with Intellectual Disabilities - Dubberly, Russell G. (Journal of the American Academy of Special Education Professionals, 2011)
This report summarizes the multi-faceted, dynamic instructional model implemented to increase positive transition outcomes for high school students with intellectual disabilities. This report is based on the programmatic methods implemented within a secondary-level school in an urban setting. This pedagogical model facilitates the use of self-determination training, functional academics, positive behavioral strategies, and normalization theory to promote community access, employment, and increased social opportunities. The various instructional methods used are dependent upon each other and require a team of educators to work collaboratively toward the common goal of students successfully transitioning from high school to adult living.